Influência da amplitude de dorsiflexão do tornozelo na cinemática dos membros inferiores e pelve durante a marcha normal e rápida - Mariana Rodrigues Carvalho De Aquino (2019)
Background: During the gait, the ankle dorsiflexion range of motion (ADF-ROM) assists the advancement of the body forward. Therefore, reduced ADF-ROM can lead to some biomechanics alterations to allow body forward motion during gait. Objectives: This cross-sectional study investigated the relationship of the ADF-ROM with lower limb and pelvis kinematics, and temporal parameters during gait in different velocities. Methods: Thirty-nine participants (16 men and 23 women) were submitted to assessment of the ADF-ROM in prone position with a goniometer. Kinematic data were collected with tridimensional motion analysis system during gait in self-selected and fast speeds. Pearson Correlation coefficients were used to test associations between clinical ADF-ROM and kinematic and temporal parameters variables. Results: Smaller ADF-ROM was associated to shorter step length (r = 0.37), smaller forefoot and midfoot sagittal plane ROM (r ≥ 0.31), rearfoot and ankle adduction peaks (r ≥ -0.31), and pelvis transverse (r ≥ 0.60) and frontal (r ≥ 0.33) planes ROM at normal and fast walking speeds. Lower values of ADF-ROM were also related to smaller knee and hip flexion peaks at normal gait during initial contact (r ≥ 0.33) at normal walking speed, and to greater forefoot plantarflexion peak at fast gait during late stance (r = 0.32) at fast walking speed. Conclusion: The reduced ADF-ROM can modify the lower limb and pelvis movements patterns during the gait in different velocities, and therefore need to be assessed in individuals with clinical conditions in these segments that can be related to gait alterations.